The Importance of Highly Engaged School-University Partnerships in Widening Participation Outreach. - Zacharias, Nadine; Mitchell, Geoffrey (Student Success v.11 n.1 p.35-45 https://doi.org/10.5204/ssj.v11i1.1458, 2020)
In Australia, there has been a sustained investment in widening participation activities by the federal government through the Higher Education Participation and Partnership Program (HEPPP) and a sustained effort by universities and their partner schools to create high-quality widening participation programs. However, there is limited longitudinal evidence on if and how these widening participation activities influence the application rates to university by school leavers from low socio-economic status (SES) backgrounds. This article draws on a large mixed-methods study which aimed to investigate differences in university application rates between students from low SES backgrounds in urban versus rural, regional and remote (RRR) schools in Queensland. The research found that widening participation programs had a positive and statistically significant influence on application rates to university in highly engaged schools. We propose the concept of a virtuous circle of sustained widening participation activity to explain the positive results in highly engaged schools. [Author abstract]